Sym the power of struggle - Roces, Alfredo R.; Gillis, Sandie (Mandaluyong City, Philippines The Crucible Workshop, 2010)
Life story and art works of Sofronio Ylanan Mendoza, well known by the name Sym.
FA-2882g donated by Sofronio Y. Mendoza
Keywords: Art -- Collectors and collecting -- Philippines; Artists -- Philippines